Effects of nickel sulphate and lead acetate trihydrate on heavy metal stress-related gene activities in forage pea (Pisum sativum ssp. arvense L.) in Türkiye - Mesci, Seda; Çatal, Muhammed İkbal (Frontiers in Plant Science, 2025)
Researching heavy metal stress in plants is of paramount importance due to the increasing prevalence of heavy metal contamination in the environment, which poses significant risks to both plant, animal, and human health. Limited data are available on heavy metal stress-related gene responses to pollutants such as nickel sulphate and lead acetate in forage peas (Pisum sativum ssp. arvense). This study aimed to investigate how specific stress-related genes respond to stress factors such as nickel sulphate and lead acetate in this plant species. In our study, we treated three cultivars of Pisum sativum ssp. arvense with nickel sulfate (20 and 40 mg/L) and lead acetate trihydrate (20 and 40 mg/L). We then measured the expression of heavy metal stress-related genes (APX, CAT, MT, PCS) using qRT-PCR on three pea cultivars (Kurtbey, Kirazlı, and Pembe) in Rize, Türkiye. Down-regulations in high heavy metal treatments and heavy metal gene-associated stress tolerance expressions were detected. Additionally, high up-regulations in APX, CAT, MT and PCS gene expressions were detected mostly at high nickel sulphate and lead acetate trihydrate applied rates. The study presents up-to-date contributions to biochemical and molecular data on the effects of nickel sulfate and lead acetate trihydrate toxicity on pea plants. These insights may inform strategies to breed or produce more heavy metal resistant crop varieties.